Fused Deposition Modeling of Microfluidic Chips in Polymethylmethacrylate - Kotz, Frederik (Micromachines (Basel), 2020)
Polymethylmethacrylate (PMMA) is one of the most important thermoplastic materials and is a widely used material in microfluidics. However, PMMA is usually structured using industrial scale replication processes, such as hot embossing or injection molding, not compatible with rapid prototyping. In this work, we demonstrate that microfluidic chips made from PMMA can be 3D printed using fused deposition modeling (FDM). We demonstrate that using FDM microfluidic chips with a minimum channel cross-section of ~300 µm can be printed and a variety of different channel geometries and mixer structures are shown. The optical transparency of the chips is shown to be significantly enhanced by printing onto commercial PMMA substrates. The use of such commercial PMMA substrates also enables the integration of PMMA microstructures into the printed chips, by first generating a microstructure on the PMMA substrates, and subsequently printing the PMMA chip around the microstructure. We further demonstrate that protein patterns can be generated within previously printed microfluidic chips by employing a method of photobleaching. The FDM printing of microfluidic chips in PMMA allows the use of one of microfluidics’ most used industrial materials on the laboratory scale and thus significantly simplifies the transfer from results gained in the lab to an industrial product.